The Mediating Influence of Team Alignment on the Relationship between Plant Turnaround Maintenance Planning and Plant Turnaround Maintenance Performance - Akbar, Jalal ud Din; Ghazali, Zulkipli B. (International Journal of Economics and Financial Issues, 2016)
In the plant turnaround, the operating assets and machinery of the organization shut down for overhauling and some capital work. This activity is very expensive and the time allocated is very low. Therefore, a good management system is required for planning all the activities of the plant turnaround maintenance. As the number of people involved in the maintenance, process is high, so teamwork is required to carry the work of plant turnaround maintenance. The alignment of team with the goals and objectives of plant turnaround maintenance has been one of the concerns for the academics and researchers. In spite of the positive impact of the team alignment on the performance of the company, only some of the organizations consider themselves having high performance due to team alignment. The previous research finding suggests that the best turnaround methodology & tools do not guarantee turnaround success as due to many reasons. So therefore, the current study attempts to use mediating approach of alignment in Plant turnaround maintenance. The survey questionnaires distributed among the technological advance and capital-intensive organisations in Malaysia covering Oil & Gas, Petrochemical Plants, Cement Plants, Palm Oils and Power Plants with a 31 companies yielding a 31% response rate. The study found that there is a positive influence for team alignment mediating the relationship between Plant Turnaround Maintenance Planning and Performance. Keywords: Plant Turnaround Maintenance; Team Alignment; Management; Planning; Performance, Mediation JEL Classifications: J52, L25